Origin, ideology and the leadership hierarchy of Al-Shabaab movement - Shuriye, Abdi Omar (2011)
The main purpose of this research is to explore the history and origin of al-Shabaab movement in East Africa. It studies the deriving ideology and directions of al-Shabaab movement. In fact, the key objectives of this research are to investigate al-Shabaab‟s political ideology and its structural leadership, to assess the ideological relationship between al-Shabaab and Al-Qaeda, to comprehend the political future of the group and to ascertain their political and theological ideologies. The research further investigates the political ideals of al-Shabaab. It is crucial to underscore al-Shabaab‟s understanding of the shar„ia; the general will of God and its political, social and religious implications. Put differently, this research endeavors to study the political viewpoints, aspirations and talents of al-Shabaab. The study limits itself to and concentrates on the movement within and in relation to East African political settings, history and development. The research employs library-based methodology in seeking wide-range conclusions. In addition, the methodology, partly, involved collecting field data in a form of informal interviews and surveys, but it is mainly an analytical and evaluative approach. The importance of this study lies on the fact that it examines a current issue which draws international attention. The group constitutes obdurate and dogmatic elements and individuals of originally Somali‟s salafi movements. The initial findings of this research are that al-Shabaab‟s ideology must have originated outside Somalia. The research therefore investigates the leadership structure of al-Shabaab and its organizational settings. My findings indicate that al-Shabaab operate in a flexible multiple cells organizational leadership structure whose components are independent.